MAJAS SARKASME DALAM PENULISAN KOMENTAR PADA "5 IRONI AKIL MOCHTAR, KETUA MK YANG DITANGKAP KPK" - nfn Irfariati (Madah: Jurnal Bahasa dan Sastra, 2015)
As a Chairman of the Constitutional Court that is used to be associated with the law, it is unfortunate if Akil Mochtar ultimately can not escape from the law itself over what he had done. The crimes committed have forced him to leave the position and accepted the punishment, both the law and the punishment of public justice. Criticism and scathing comments from the public flew due to deep disappointment at the head of this legal institution. The purpose of this study is to describe the form of sarcasm figure of speech  contained in the group www.merdeka.com which commented and described a variety of language used in the disclosure of sarcasm figure of speech group www.merdeka.com comments (5 Ironi Akil Mochtar, Ketua MK yang ditangkap KPK. ("5 irony Akil Mochtar, who was arrested KPK Chief Justice"?) This study applied a qualitative descriptive method and discourse analysis technique. This study showed that the figure of speech used were in the form of sarcasm words and phrases. Types of the words used were in the form of adjective, noun, and verb. While the language variation used based on the meaning and the language used. The language variation used can be divided into a figure of speech in the form of calumny, calls, and commands. They included regional languages and foreign languages. The use of local and foreign languages are not completely due to there are so many code mixing  occurred when delivering the comments.